THE CONCEPT ANDRAGOGY AND PEDAGOGY: E-LEARNING MODEL DURING COVID-19 PANDEMIC - Selicha Putri; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
This paper describes a research project that investigated the pedagogical and/or andragogical orientation preferred by undergraduate students at one of Indonesia's higher education institutions. To collect data, questionnaires were distributed to 200 undergraduate students who took the Introduction to Programming Language course, and descriptive analyses were performed. To validate the data, qualitative data from interviews was gathered and triangulated. These findings have implications for educators involved in the development of online learning applications and will be used to create a prototype of an individualized online learning environment based on pedagogy and andragogy